Does service innovation matter? An empirical study on market orientation and supply chain performance - T-Y. D.J. Cheng; C-H. V. Chen (South African Journal of Business Management, 2017)
The objective of this study was to explore how firm service innovation mediates market orientation and business performance. This paper begins with a literature review indicating the themes from which we developed our conceptual framework. Structural equation modeling based on a cross-section (n = 260) of 5 years of supply chain business data (2009–2013) in Greater China was conducted. We concluded that firm market orientation and service innovation exert significantly positive effects on business performance. In addition, the results supported our model that market orientation is mediated by the effect of service innovation on business performance. Market orientation and service innovation had a stronger combined effect on business performance than market orientation alone did. This paper provides implications for how firms can be more effectively synergized amid challenges and gain a competitive advantage in the global supply chain.
Keywords: 650